Acacia catechu(khair) Sap Wood: its Possible Commercial Utilisation - Karnik, M. G.; Bhatia, Kuldip; Dev, Inder; Lal, Jia (Indian Forester, 1971)
The studies have been made to explore the possible commercial utilization of Sap I wood of Khair. The Sap wood was analysed for its major chemical constituents and the optimum conditions to isolate cellulose suitable for cellulose based industries have been described. The chemical composition of the cellulose and its fibre dimensions have been determined. The experiments were undertaken to prepare cellulose gum and the data on its evaluation are presented in the article.